2019
DOI: 10.3390/su11051423
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Sediment Erosion Analysis in Francis Turbine

Abstract: Effective hydraulic turbine design prevents sediment and cavitation erosion from impacting the performance and reliability of the machine. Using computational fluid dynamics (CFD) techniques, this study investigated the performance characteristics of sediment and cavitation erosion on a hydraulic Francis turbine by ANSYS-CFX software. For the erosion rate calculation, the particle trajectory Tabakoff–Grant erosion model was used. To predict the cavitation characteristics, the study’s source term for interphase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…The found results are qualitatively comparable to those obtained by Rakibuzzaman et al (2019), mostly over the pressure side of the runner blade mainly at the leading edge and the trailing edge. Furthermore, Figure 24 provides depictions of the real erosion patterns in the Francis turbine taken from the Cahua hydro-power plant (Eltvik et al , 2011).…”
Section: Resultssupporting
confidence: 86%
“…The found results are qualitatively comparable to those obtained by Rakibuzzaman et al (2019), mostly over the pressure side of the runner blade mainly at the leading edge and the trailing edge. Furthermore, Figure 24 provides depictions of the real erosion patterns in the Francis turbine taken from the Cahua hydro-power plant (Eltvik et al , 2011).…”
Section: Resultssupporting
confidence: 86%
“…To reduce the influence of grid number on computational results, a grid dependency study at the rated head (15 m) operating condition (GV 60 • and RV 24 • ) was conducted. This showed that the efficiency deviation was less than 1% [38,39], as shown in Figure 7. The grid independency test was carried out based on the grid convergence index (GCI) method [40][41][42].…”
Section: Geometrical Model and Meshingmentioning
confidence: 78%
“…Table 5 illustrates CFD performance and experimental results for the tubular turbine. As shown in Table 6, the average deviation of the head was 0.231%, and the flow rate deviation was only 2.105% at a rotational speed of 496 rpm [39,49]. The power output and efficiency of the turbine were different due to the different runner vane openings in the experiment and simulation.…”
Section: Validation Of Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations